RESPON PERTUMBUHAN BIBIT KAWISTA (Limonia acidissima L.) TERHADAP PEMBERIAN PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) - Siska Dwi Lestari; Nora Augustien Kusumaningrum; Ida Retno Moeljani (UPN VETERAN JAWA TIMUR, 2020)
Kawista (Limonia acidissima L.) is a slow-growing annual plant whose causing decline population, necessary to be an effort to provide quality kawista seed on a large scale. The purpose of this research is to know the effect of PGPR concentration on the growth of kawista seed. Kawista seeds were planted in polybags placed in the experimental field of Agriculture Faculty UPN “Veteran” of East Java in November 2019 – February 2020. This research was compiled using a completely randomized design (RAL) one factor of PGPR concentration with 6 treatments (0, 5, 10, 15, 20, and 25) ml/L and each treatment was repeated 4 times. Parameters measured were increase in seedling height, increase in number of leaves, increase in stem diameter, increase the length of primary root, number of roots, and seed strength. Data were analyzed by F test and treatment was analyzed by BNJ at the level 5%. The result research showed no significant difference in the increase in seedling height, increase in number of leaves, increase in stem diameter,and seed strength. The response of kawista seed to PGPR concentration of 15 ml/L increase the length of primary root by 15,03 % and number of roots by 54,43 % compared without application of PGPR.